2009
DOI: 10.1111/j.1365-2133.2009.09351.x
|View full text |Cite
|
Sign up to set email alerts
|

MYCgene numerical aberrations in actinic keratosis and cutaneous squamous cell carcinoma

Abstract: MYC gains and amplifications are frequent cytogenetic abnormalities in SCCs and may play a relevant role in promoting SCC undifferentiation and tumoral progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 21 publications
6
43
0
1
Order By: Relevance
“…Regarding cSCC, gains and amplifications of MYC and EGFR have recently been reported by our group (Toll et al, 2009(Toll et al, , 2010 and we found that aberrations involving MYC were more frequent in moderately to poorly differentiated cSCCs than in well differentiated counterparts. In the present study, 8 of 14 cSCC with CKS1B amplification metastasized to mcSCC.…”
Section: Cks1b In Cutaneous Squamous Cell Carcinomamentioning
confidence: 65%
“…Regarding cSCC, gains and amplifications of MYC and EGFR have recently been reported by our group (Toll et al, 2009(Toll et al, , 2010 and we found that aberrations involving MYC were more frequent in moderately to poorly differentiated cSCCs than in well differentiated counterparts. In the present study, 8 of 14 cSCC with CKS1B amplification metastasized to mcSCC.…”
Section: Cks1b In Cutaneous Squamous Cell Carcinomamentioning
confidence: 65%
“…11,12 They seem to have a relevant role in the biological behavior of several carcinomas. Frequent integration of HPV at 8q24 in cervical carcinoma cell lines has also been reported.…”
mentioning
confidence: 99%
“…Additional molecular events associated with AK formation include increased activation or levels of SFKs, EGFR, Myc, and ATF-3 (30)(31)(32)(33). In addition, decreased levels of inositol polyphosphate 5′-phosphatase have also been reported in AKs, which could result in increased PI3K/Akt signaling (34).…”
Section: Introductionmentioning
confidence: 99%